LEGAL REGULATION OF THE POLITICAL RIGHTS OF PEOPLE WHO HAVE ACQUIRED IRAQI NATIONALITY - Zeyad Tariq Ibrahim; Prof. Fadwa Al-kahwaji (Scholars Digest Publishing, 2024)
Human rights were granted with the interest of countries of different orientations and regardless of Its governance systems. They decided to approve these rights in their national constitutions, and among these rights is the right to nationality, as it is one of the basic rights of the individual that cannot be dispensed with and according to which the rights of the individual and his national character are determined. Therefore, the laws have stipulated various cases for acquiring nationality, including acquiring it through filiation and naturalization after certain conditions are met. It is not permissible to deprive him of it arbitrarily, but in Iraq, the individual enjoys it He has civil and political rights when he acquires Iraqi nationality. Among the civil rights that he acquires is the right to life, which is considered one of his natural rights that may not be infringed upon or deprived of. As for his political rights, they include his right to elect and nominate, on the basis of which a foreigner who has acquired Iraqi nationality can be distinguished. About the Iraqi National
Keywords: Acquired nationality, constitution, political rights, original nationality, Iraqi nationality law.